Expert support system for occupational therapist in the identification of sensory profile - Thais Caroline Pereira; Deborah Ribeiro Carvalho; Claudia Maria Cabral Moro
Introduction Based on the increasing usability of technology in healthcare, this paper discusses the use of an expert system (ES) to identify the sensory profile of patients starting Occupational Therapy, allowing the professional to make assertive decisions in establishing priorities in the therapeutic plan.Objective To develop a decision support system from the Infant/Toddler Sensory Profile.Method Structuring of an ES based on Infant/Toddler Sensory Profile, from terms translation into Portuguese, identification of variables and domain values involved, and construction of production rules.Results Twelve variables were registered for the construction of the ES, 6 of these were treated as goal-variables, 20 rules being built.Conclusion This ES is an important support to the occupational therapist in the decision-making process of treatment plans, determining priorities and respecting the sensory profile of each child. In addition, it must be noted that there is no equivalent system.